(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
First step of health care system is Pre-hospital emergency service to provide treatment facilities to patients. Before admission of patients to hospital, provision of services to patients by pre hospital emergency service causes satisfaction or dissatisfaction for the patients with overall health care system of a society. This study was conducted to measure the satisfaction of patients with Punjab Emergency Service Rescue 1122 in the city of Chiniot, Punjab. There were 340 conscious patients at the time of emergency were included in this study by using systematic sampling technique. Data were analysed by a computer software Statistical Packages for Social Sciences (SPSS). Results of the univariate analysis showed that the majority of the users of the service were male and belong to rural area of the Chiniot 236 and 225 respectively. The majority of the respondents 250 experienced road traffic accidents. The results showed that the satisfaction of the patients from condition of the ambulance, response time, behaviour of the rescue team, efficiency of the service and professionalism of rescue crew was very high. The independent variables including condition of ambulance, behaviour of rescue team and professionalism of team showed a strong positive relationship with patients’ satisfaction. While response time of the ambulance showed a strong negative correlation. The results of the study revealed a very high level of satisfaction of the patients with Punjab Emergency Service Rescue 1122 Chiniot.